Chemometric Comparison of High-Pressure Processing and Thermal Pasteurization: The Nutritive, Sensory, and Microbial Quality of Smoothies - Marko Škegro; Predrag Putnik; Danijela Bursać Kovačević; Ana Petra Kovač; Lidija Salkić; Iva Čanak; Jadranka Frece; Sandra Zavadlav; Damir Ježek (Foods, 2021)
This study investigated the status of bioactive compounds (phenolic compounds, carotenoids, and vitamin C), changes in color performance, and microbiological quality in smoothies preserved by high-pressure processing (HP) and thermal pasteurization (P) during cold storage at 4 °C for 21 days. Chemometric tools were used to select relevant variables that represent the most useful information for the fast and accurate quality assessment of smoothies. HP was performed at 350 and 450 MPa for 5 and 15 min at room temperature, respectively, while P was performed at 85 °C for 7 min. Smoothies were prepared by blending juices of apple (50%, v/v), carrot (20%, v/v), chokeberry (5%, v/v), Indian banana puree (10%, w/v), and almond drink (15%, v/v). The results obtained indicated that lower pressures with a shorter duration of HP showed higher levels of bioactive compounds in the smoothies, compared to the control samples. Compared to P, the HP samples exhibited a greater stability of bioactive compounds during shelf life. HP was found to be highly effective in reducing the native microflora of the smoothies, without subsequent microbial activation during storage. This study demonstrated the usefulness of the chemometric approach in interpreting complex datasets for the effective quality assessment of smoothies treated with different preservation technologies.